A barrier-to-autointegration factor promotes white spot syndrome virus infection in a crustacean Cherax quadricarinatus. Issue 105 (October 2020) - Liu, Ling-ke; Gao, Yan; Gao, Rui-lin; Li, Dong-li; Zhang, Qiu-xia; Wang, Ke-jian; Liu, Hai-peng
Abstract: Barrier-to-autointegration factor (BAF) is a highly conserved DNA binding protein that participates in a variety of biological processes such as transcription, epigenetic regulation and antiviral immunity in vertebrates. However, the function of BAF is poorly understood in crustaceans. In this study, we identified a barrier-to-autointegration factor ( CqBAF ) from red claw crayfish Cherax quadricarinatus, which was responsive to white spot syndrome virus (WSSV) infection. The full-length cDNA sequence of CqBAF was 544 bp, including an open reading frame of 273 bp encoding 90 amino acids, a 107 bp of 5′-Untranslated Regions (5′-UTR) and a 164 bp of 3′-UTR. Gene expression analysis showed that CqBAF was distributed in all tissues examined with the highest expression in the crayfish haematopietic tissue (Hpt), which protein expression was also significantly up-regulated by WSSV infection in Hpt cells. Furthermore, the transcripts of both an immediate early gene IE1 and a late envelope protein gene VP28 of WSSV were clearly reduced in Hpt cells after gene silencing of CqBAF . Importantly, the promoter activity of two immediate early genes of WSSV, including WSV051 and IE1, was strongly enhanced by the increased phosphorylation of Cq BAF, which also facilitated the accumulation of Cq BAF protein in the cytoplasm of Sf9 cells. Taken together, these data suggest that Cq BAF is likely to increase the replication of WSSV by promoting the transcription of viral immediate early genes, probably regulated by phosphorylation of Cq BAF, which sheds new light on the molecular mechanism of WSSV infection. Highlights: CqBAF is responsive to WSSV infection. CqBAF promotes the replication of WSSV. The increased phosphorylation of CqBAF may enhance the promoter activity of WSSV IE genes. The phosphorylation of CqBAF promotes its accumulation in the cytoplasm.